1999
DOI: 10.1095/biolreprod61.3.657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inflammatory Mediators on the Electrophysiology of the Human Oviduct1

Abstract: The effects of histamine and other inflammatory mediators on the electrophysiology and intracellular free calcium ([Ca(2+)](i)) of human oviductal epithelial cells, grown as a polarized layer in primary culture, were studied. Transepithelial potential difference (PD) and short-circuit current (I(scc)) were recorded using a modified Ussing chamber. Resistance (R) was calculated from the measurements of PD and I(scc). Basally applied histamine produced transient increases in PD and I(scc) with a small decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Conversely, histamine interferes with cellular transportation by regulating the ion transporters rather than altering the paracellular permeability and it increases electrical resistance of the human bronchial epithelial cells without increasing the permeability through the tight junctions, (Devalia et al 1994) an event which was also demonstrated in the porcine proximal colon cells (Ahrens et al 2003). Histamine also changes the electrochemical profile of fallopian tube cells and ovaries (Downing et al 1999(Downing et al , 2002 in a dose-dependent manner, while…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, histamine interferes with cellular transportation by regulating the ion transporters rather than altering the paracellular permeability and it increases electrical resistance of the human bronchial epithelial cells without increasing the permeability through the tight junctions, (Devalia et al 1994) an event which was also demonstrated in the porcine proximal colon cells (Ahrens et al 2003). Histamine also changes the electrochemical profile of fallopian tube cells and ovaries (Downing et al 1999(Downing et al , 2002 in a dose-dependent manner, while…”
Section: Discussionmentioning
confidence: 99%
“…H 1 receptors seem to play the most important role; in airway epithelia (Flynn et al 2009, Chan et al 1987, in vascular epithelia (Flynn et al 2009), in nostrils (Yang et al 2003), in Fallopian tubes and ovaries (Downing et al 1999(Downing et al , 2002 and in human colon (Keely et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its receptor is present in the oviducts of humans (43) and cows (44). Platelet-activating factor has been shown to affect the electrophysiology of human oviducts (45) and increase the intracellular calcium concentration (46) and proliferation (47) of bovine oviductal cells. In mares, embryonic prostaglandin E 2 has been proposed as the agent responsible for the differential transport of embryos and oocytes in the oviduct (48).…”
Section: Discussionmentioning
confidence: 99%
“…They were then placed in a final volume of 30 μL of FSW in the middle of an area 1 cm 2 in diameter of a slide previously waterproofed with a ring of white vaseline. In the first series of experiments, the branchial portions were incubated for 10 min with various solutions (1, 10, 100, 1,000 μM) of histamine (Fluka) to identify the concentration of histamine at which the maximum response of the CBF occurs, as reported in vitro for mammalian ciliary epithelia (Lurie et al, ; Dowing et al, ; Del Donno et al, ). Then, the branchial portions were incubated with 30 μL of various solutions in FSW as follows: (1) FSW as control for 10 min; (2) a 100 μM solution of histamine for 10 min; (3) a 100 μM solution of a histamine receptor antagonist: chlorpheniramine maleate (CAS: 132‐22‐9) as HRH1 antagonist, ranitidine hydrochloride (CAS: 66357‐35‐5) as HRH2 antagonist, and clobenpropit dihydrobromide (CAS: 145231‐45‐4) as HRH3 antagonist.…”
Section: Methodsmentioning
confidence: 99%